Лучшие люди России: энциклопедия ([руководитель проекта и главный редактор А. В. Бруй]) - Бруй А. В. (2005)
Экземпляры: ЧЗ (20150914) / Инвентарный номер: 42434 / Цена: 300 / Сис.шифр: Я20 / Авт.знак: Л 876 / ГРНТИ: 00 / ББК: Я20